Leveraging The Ansoff Matrix for Strategic Growth in Packaged Food Micro-Enterprises - Qomaro, Galuh Widitya; Nasrulloh, Nasrulloh; Salleh, Ahmad Zaki (Universitas Trunojoyo Madura, 2024)
Micro-enterprises are vital for local economic development, yet they often struggle with limited strategic capacity, particularly in regions where socio-cultural and religious factors strongly influence business practices. This study addresses the strategic management gaps among packaged food micro-enterprises in Bangkalan, Indonesia, with a focus on how these businesses navigate challenges while leveraging growth opportunities. The research fills a critical gap by integrating cultural and religious dynamics such as the importance of halal compliance-into established strategic frameworks like the ANSOFF Matrix.Using a qualitative methodology, the study conducted in-depth interviews with 23 micro-entrepreneurs to explore their strategic behaviors, market approaches, and challenges. The thematic analysis revealed the alignment and divergence of practical strategies with theoretical models, offering insights into how entrepreneurs manage risks and pursue growth.Findings indicate that while most businesses prioritize market penetration and product development, significant barriers-including inadequate access to resources and strategic knowledge-impede diversification and market expansion. Halal certification emerged as a pivotal yet challenging factor in market dynamics. The study concludes that strategic support, such as targeted training and collaborations with local institutions, can empower micro-enterprises to enhance competitiveness and contribute to sustainable development.